2019
DOI: 10.3389/fmars.2019.00465
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Phylogeny and Species Diversity of Chelidoperca (Teleostei: Serranidae) From the Western Pacific Ocean by an Integrated Approach in Systematics, With Descriptions of Three New Species and a Redescription of C. lecromi Fourmanoir, 1982

Abstract: With 11 species, the genus Chelidoperca is a small group of teleost fishes belonging to the Serranidae. They are bottom-dwelling fishes living on continental shelves/slopes in offshore areas or on remote seamounts/banks at depths ranging from around 40-400 m mostly in the tropical Indo-West Pacific. Over the past few years, efforts have been made to resolve the taxonomy of Chelidoperca, and subsequently four new species were described. However, these recent advances were made with a traditional approach (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…The species-delimitation methods based on genetic distance (ABGD, SPN) and coalescence (GMYC, BPP) showed incongruent results for the six genes (Fig 2 , Table 4). Among these methods, the highest number of species was delimited by the BPP analyses (25), whereas the most conservative results were obtained from GMYC (16 ± 10) (S5 and S6 Figs, S2 Table ). Moreover, similar species numbers resulted from the ABGD (22 ± 6) and SPN (23 ± 5) analyses.…”
Section: Species Delimitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The species-delimitation methods based on genetic distance (ABGD, SPN) and coalescence (GMYC, BPP) showed incongruent results for the six genes (Fig 2 , Table 4). Among these methods, the highest number of species was delimited by the BPP analyses (25), whereas the most conservative results were obtained from GMYC (16 ± 10) (S5 and S6 Figs, S2 Table ). Moreover, similar species numbers resulted from the ABGD (22 ± 6) and SPN (23 ± 5) analyses.…”
Section: Species Delimitationmentioning
confidence: 99%
“…This has been overcome by methods that encompass genetic distance and coalescent approaches, which have proven very useful and been widely used for a range of taxa [15,[17][18][19][20]. Accordingly, the use of several methodologies and data sets to delimit species (i.e., integrative approaches) is highly recommended, and subsequently, the achievement of congruent results across the methods is likely to prove most useful for framing reliably supported species boundaries [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, after re-examining them based on a mitochondrial gene, we found that they are genetically distinct from each other. The purpose of this study is to validate the specimen collected from the Solomon Sea as representing a new species of Luciobrotula by using an integrated approach in taxonomy (Dayrat 2005;Hung et al 2017;Lo et al 2017;Lee S.-H. et al 2019).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…Despite intensive sampling efforts from either local organizations in Taiwan or international expeditions through the TDSB for over a decade, only a few specimens were made available for scientific investigations. The difficulty in sampling has limited our understanding of biodiversity, phylogeny, biogeography, and ecology of deep-sea fishes such as those from the rare genus Luciobrotula or others (e.g., Chelidoperca Boulenger, 1895) (Lee S.-H. et al 2019). In spite of that, in this study we successfully uncover the hidden diversity of the Luciobrotula in the West Pacific using an integrated approach in taxonomy and conduct the first phylogenetic study of Luciobrotula.…”
Section: Key To All Known Species Of Luciobrotula Smith and Radcliffe 1913mentioning
confidence: 99%
“…In the recent decade, several new species have been described on the basis of morphology and molecular sequence data (Bineesh et al ., 2013; Lee et al ., 2019; Matsunuma et al ., 2018; Matsunuma & Motomura, 2016; Ogino et al ., 2020; Psomadakis et al ., 2021; Williams & Carpenter, 2015). In addition, the taxonomy of several species has been revised through redescription and species verification (Bineesh et al ., 2014; Matsunuma, 2016; Matsunuma & Tashiro, 2020).…”
Section: Introductionmentioning
confidence: 99%